New Trends in the Co-crystallization of Active Pharmaceutical Ingredients - Veerendra K. Nanjwade, F. V. Manvi, Shamrez Ali. M, Basavaraj K. Nanjwade, Meenaxi M. Maste (Journal of Applied Pharmaceutical Science)
Pharmaceutical materials science being a fundamental branch that continuously provides important insights, theories, and technologies to formulation sciences. The recent advances in this area have brought the possibility to produce pharmaceutical materials by design. In particular, the formation of co-crystals, i.e. crystalline molecular complexes of twoor more neutral molecules, represents a potential route to achieve pharmaceutical materials with improved properties of interest, including dissolution rate and stability under conditions of high relative humidity. Co-crystals consists of API and a stoichiometric amount of a pharmaceutically acceptable co-crystal former. Pharmaceutical co-crystals are nonionic supramolecular complexes and can be used to address physical property issues such as solubility, stability and bioavailability in pharmaceutical development without changing the chemical composition of the API. These can be constructed through several types of interaction, including hydrogen bonding, pi-stacking, and van der Waals forces. Phase transformations induced during processing/storage affects the mechanisms of conversion of crystalline drugs to co-crystals. Pharmaceutical co-crystals considered better alternatives to optimize drug properties could play a major part in the future of API formulation and can be employed for chiral resolution. This review introduces co-crystals as an emerging class of pharmaceutical materials, focusing on the experimental methods applicable to their crystallization. In addition, the examples illustrating how the co-crystal approach can be utilized to enhance the specific properties of pharmaceutical solids, such as dissolution rate of poorly-water soluble APIs and physical stability of moisture-labile APIs.
Keywords: Co-crystal, API, Phase transformations, Supramolecular complexes, Physical stability.